In Search of Lost Architecture: The Indoor Swimming Pool of Marbella, Spain, by Paolo Portoghesi and Vittorio Gigliotti. - Santana-Guzmán, Antonio Jesús (Springer Nature, 2024)
Between 1971 and 1972 an indoor swimming pool was designed and built in the municipality of Marbella as a service for a hotel. The project was carried out in Italy by the architect Paolo Portoghesi and the engineer Vittorio Gigliotti. In order to obtain the necessary permits, the plans had to be signed by architects who had a Spanish degree or who had homologated the one obtained in another country. For this reason, Alberto Balbontín de Orta and Antonio Delgado Roig were involved and directed the works. In 1997, for reasons of maintenance and speculation with the site, the building was demolished. This research highlights the value of the disappeared building and underlines the influences that were taken as a reference for its design. The rich culture of its designers, Portoghesi and Gigliotti, is demonstrated in this example of post-modern architecture in which the links with memory and nature stand out.
https://www.springernature.com/gp/open-science/policies/book-policies
Keywords: Arquitectura contemporánea; Postmodernismo; Alberto Balbontín de Orta; Antonio Delgado Roig; Vittorio Gigliotti; Paolo Portoghesi; Puerto Banús; Post-modern architecture